Speech evaluation with and without palatal obturator in patients submitted to maxillectomy Avaliação de fala com e sem obturador de palato em pacientes submetidos à maxilectomia - Viviane de Carvalho-Teles; Maria Inês Pegoraro-Krook; José Roberto Pereira Lauris (University of São Paulo, 2006)
Most patients who have undergone resection of the maxillae due to benign or malignant tumors in the palatomaxillary region present with speech and swallowing disorders. Coupling of the oral and nasal cavities increases nasal resonance, resulting in hypernasality and unintelligible speech. Prosthodontic rehabilitation of maxillary resections with effective separation of the oral and nasal cavities can improve speech and esthetics, and assist the psychosocial adjustment of the patient as well.The objective of this study was to evaluate the efficacy of the palatal obturator prosthesis on speech intelligibility and resonance of 23 patients with age ranging from 18 to 83 years (Mean = 49.5 years), who had undergone inframedial-structural maxillectomy. The patients were requested to count from 1 to 20, to repeat 21 words and to spontaneously speak for 15 seconds, once with and again without the prosthesis, for tape recording purposes. The resonance and speech intelligibility were judged by 5 speech language pathologists from the tape recordings samples. The results have shown that the majority of patients (82.6%) significantly improved their speech intelligibility, and 16 patients (69.9%) exhibited a significant hypernasality reduction with the obturator in place. The results of this study indicated that maxillary obturator prosthesis was efficient to improve the speech intelligibility and resonance in patients who had undergone maxillectomy. A maioria dos pacientes submetidos a ressecções de maxila apresenta alterações nas funções de fala e de deglutição. O acoplamento das cavidades oral e nasal resulta em hipernasalidade de graus variados e no comprometimento da inteligibilidade de fala. A reabilitação protética tem como objetivo separar as cavidades oral e nasal podendo reduzir as alterações de ordem estética, funcional e ainda melhorar o ajustamento social deste paciente. Este trabalho teve como objetivo avaliar a eficácia da prótese obturadora de palato quanto à inteligibilidade e à ressonância de fala em 23 pacientes com idades entre 18 e 83 anos (Média = 49,5 anos) submetidos à maxilectomia inframeso-estrutura. Para fins de gravação, os pacientes foram solicitados a realizar oralmente a contagem de números de 1 a 20; a repetir 21 palavras balanceadas foneticamente e a realizar 15 segundos de conversa espontânea, uma vez com e outra vez sem a prótese. Este material de fala foi apresentado a 5 fonoaudiólogos para os julgamentos de inteligibilidade e ressonância de fala. Os resultados revelaram que 82,6% apresentaram uma melhora significante da inteligibilidade de fala e 69,6% obtiveram uma redução significante da hipernasalidade após a adaptação da prótese obturadora de palato. Os resultados deste estudo demonstraram que a prótese obturadora de palato mostrou-se eficaz na melhora da inteligibilidade e ressonância de fala dos pacientes submetidos à maxilectomia.